Fatty acid kinase A is an important determinant of biofilm formation in Staphylococcus aureus USA300. (December 2015) - Sabirova, J.; Hernalsteens, J-P; De Backer, S.; Xavier, B.; Moons, P.; Turlej-Rogacka, A.; De Greve, H.; Goossens, H.; Malhotra-Kumar, S.
Abstract Background Methicillin-resistantStaphylococcus aureus (MRSA)-USA300 is notorious for its ability to cause community- and healthcare-acquired infections, which are even more difficult to treat when associated with a biofilm phenotype. We aimed to characterize the genetic determinants of biofilm formation in a USA300 skin abscess isolate (UAS391) that formed prolific biofilms. Methods USA300S. aureus strains, TCH1516 and FPR3757, were found to be closely related based on whole genome mapping (Argus™ Optical Mapping System, Opgen Inc, Gaithersburg, USA) to UAS391 (96.3-99.1 % similarity, P=0.0151), however differed markedly in biofilm formation (P=0.0001) on a dynamic assay (BioFlux 200, Fluxion Biosciences, USA). Comparison of whole genome sequences of these strains identified differences in a total of 18 genes. Corresponding Tn (bursa aurealis -bearing) knockout mutants in these target genes were obtained from a publicly available mutant library of the same clonal lineage (USA300-JE2) and were characterized phenotypically for biofilm formation. Tn mutants showing significant differences in biofilm formation were utilized for transduction into a plasmid-cured erythromycin-sensitive derivative of UAS391 and for complementation experiments. All strains were tested on the dynamic assay, and 17h-biofilms were stained (SYTO9, Life Technologies) and fluorescence intensity quantified by microscopy (Zeiss, ImageJ). Gene expression levels in Tn and transduced mutants were studied by quantitative reverse transcriptase PCR (StepOnePlusTM, Applied Biosystems®). Results Comparison of the sequenced genomes of TCH1516, FPR3757 and UAS391 yielded a limited number of variant genes (n=18) that were hypothesized to account for the observed difference in biofilm-forming capacity. Screening of Tn mutants disrupted in these target genes identified one mutant (NE229) bearing a transposon insertion in SAUSA300_1119 (fakA ), which exhibited increased biofilm formation similar to UAS391 (P=0.9320). Transduction experiments confirmed thatfakA ::Tn corresponded to 1.9- to 4.6-fold increase in biofilm formation depending on the USA300 strain background (P≤0.0007), while complementation of the TCH1516 wild-typefakA allele in UAS391 resulted in a 4.3-fold reduction in biofilm formation (P<0.0001). Conclusions This sequential approach, consisting of strain typing, genome comparison and functional genomics, identifiedfakA, a recently described fatty acid kinase inS. aureus that is essential for phospholipid synthesis and also impacts the transcription of numerous virulence factors, as a negative regulator of biofilm formation inS. aureus USA300.